Primeiros socorros no ambiente escolar: o que fazer? Reflexões acerca do atendimento de saúde por educadores da Educação Infantil - Scolari, Daniela (Universidade do Vale do Rio dos Sinos, 2023)
The objective of this study is to evaluate the level of knowledge of Early Childhood Education educators at Colégio Anchieta from Porto Alegre regarding first assistance in complications and accidents that happen to children aged 3 to 5 years. Through qualitative research, based on a semi-structured interview with 19 people, all Early Childhood Education teachers at the school, we sought to find out how prepared these professionals are to provide first aid care in the school environment. The results indicate that the majority has basic knowledge and non-confidence, demonstrating the need for training in this area and continuing education projects. It is suggested the implementation of a continuing education program in first aid, aiming to develop prevention, intervention and promotion of school health, with a theoretical and practical basis, thus establishing more confidence in teachers and employees when providing first aid.
Keywords: Primeiros socorros; Escola; Atendimento; Professores; First aid; School; Service; Teachers